2022
DOI: 10.1021/acssuschemeng.1c07523
|View full text |Cite
|
Sign up to set email alerts
|

Fully Bio-Based High-Performance Thermosets with Closed-Loop Recyclability

Abstract: Thermosets are important commodity polymeric materials, but they are rarely biorenewable and recyclable. Although some previously reported bio-based aromatic thermosets with a high aromatic content have good thermal/mechanical properties, the mechanical properties of fully bio-based vitrimers are relatively poor owing to low aromatic contents. To address this important issue, vanillin-based dialdehyde and trialdehyde containing high aromatic content were synthesized, and renewable diamines containing short ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…The low aromatic content and the long aliphatic chain length in the crosslinking network weakened the tensile strength. 36 However, the elongation at break was greatly enhanced, and the high toughness and the elastic nature broadened the application area of the vitrimer synthesized in the present work.…”
Section: Resultsmentioning
confidence: 79%
“…The low aromatic content and the long aliphatic chain length in the crosslinking network weakened the tensile strength. 36 However, the elongation at break was greatly enhanced, and the high toughness and the elastic nature broadened the application area of the vitrimer synthesized in the present work.…”
Section: Resultsmentioning
confidence: 79%
“…Such a closed-loop recycling method based on an imine exchange reaction was also a research direction and interest of researchers in recent years. [60][61][62] The exchange reaction of imine bonds can be carried out at room temperature, unlike other dynamic bonds that require high temperature, which provides the potential for the closed-loop chemical recycling of thermosets based on dynamic imine bonds. In 2020, Guo and co-workers 63 prepared a cross-linked network based on imine bonds through the reaction between aldehyde-terminated polybutadiene and tris(2-aminoethyl) amines.…”
Section: Schiff Basementioning
confidence: 99%
“…It can be observed that although the tensile strength, modulus and elongation at break of A 7 P 3 -D230 decreased gradually, the tensile strength still retained 86.1% and 66.8% after one and two reprocessing steps in comparison with the original A 7 P 3 -D230. Two main reasons can justify this result: (1) during the reprocessing process, only C = N, as the dynamic covalent bond, can be repaired, while other covalent bonds such as C − C, P-O and P = O cannot be repaired after break [35,51]; (2) epoxy vitrimer was probably degraded during the hot pressing [52,53].…”
Section: Reprocessing Recyclability and Repairability Of Epoxy Vitrimermentioning
confidence: 99%
“…The decomposition mechanism and rearrangement mechanism of the crosslinking network of thermosets are the uniqueness of vitrimer materials [54]. Due to the reversible reaction properties of Schiff base bonds, epoxy vitrimer can be degraded via the exchange reaction between amino and imine groups under acidic conditions [26,52]. To prove this hypothesis, A 7 P 3 -D230 was immersed in a mixed solution of 1M HCl/THF (v:v = 2:8) and stirred continuously at 60 ºC for 60 min, as shown in Fig.…”
Section: Reprocessing Recyclability and Repairability Of Epoxy Vitrimermentioning
confidence: 99%